2017
DOI: 10.2147/clep.s121991
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on the efficacy–effectiveness gap: comparison of randomized controlled trials and observational studies of glucose-lowering drugs

Abstract: AimTo identify a potential efficacy–effectiveness gap and possible explanations (drivers of effectiveness) for differences between results of randomized controlled trials (RCTs) and observational studies investigating glucose-lowering drugs.MethodsA systematic literature review was conducted in English language articles published between 1 January, 2000 and 31 January, 2015 describing either RCTs or observational studies comparing glucagon-like peptide-1 analogs (GLP-1) with insulin or comparing dipeptidyl pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…This is described as the "efficacy-effectiveness gap" and may be attributed to the strict inclusion/ exclusion criteria used for clinical trials and lack of external validity. 15 While it is challenging to draw a true comparison, SVR rates from the 12-week group in the present study were high and do not appear to be different from rates achieved in the SOLAR-1 trial. Patients evaluated at UWMC in the 12-week group may have been a healthier population compared to those assessed in the SOLAR-1 trial as there were no patients with decompensated cirrhosis, while 26% of patients in the SOLAR-1 trial had this There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 48%
“…This is described as the "efficacy-effectiveness gap" and may be attributed to the strict inclusion/ exclusion criteria used for clinical trials and lack of external validity. 15 While it is challenging to draw a true comparison, SVR rates from the 12-week group in the present study were high and do not appear to be different from rates achieved in the SOLAR-1 trial. Patients evaluated at UWMC in the 12-week group may have been a healthier population compared to those assessed in the SOLAR-1 trial as there were no patients with decompensated cirrhosis, while 26% of patients in the SOLAR-1 trial had this There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 48%
“…A systematic review by Ankarfeldt, et al explored a potential efficacy-effectiveness gap as a driver of the differences in observed impact of glucose-lowering drugs between observational studies and randomized controlled trials. [5] They dichotomized papers as either being pure randomized controlled trials reflecting efficacy designs or observational studies reflecting effectiveness designs and compared mean observed effect sizes in each group. Although, Ankarfeldt, et al did not identify an efficacy-effectiveness gap (possibly as a result of limited sample size and confounding), significant gaps between efficacy and effectiveness outcome have been observed for many interventions.…”
Section: 0 Significance Of Distinguishing Effectiveness and Efficacmentioning
confidence: 99%
“…However, specific details on the mechanisms that drive individual response to temozolomide treatment in clinical practice, or on the drivers of real-world patient-level treatment effectiveness, are unknown (van Genugten et al, 2010;Eichler et al, 2011;Liu et al, 2016). To study these personal responses, traditional cohort-oriented methods, such as the Kaplan-Meier survival techniques currently used in pharmacoepidemiology (Strom and Kimmel, 2006) for investigating real-world evidence (RWE) data, have shown to be inadequate because of their difficulties to cope with heterogeneous patient populations; their restrictive assumptions regarding linear relationships among variables; their inability to provide patient-level predictions; and their inability to infer causality (Ankarfeldt et al, 2017;Arora et al, 2019).…”
Section: Introductionmentioning
confidence: 99%